USM, EOPP, MDC, UP COLLABORATES TO SPEARHEAD ECO-ENGINEERING PROJECTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 1 July 2016 – Universiti Sains Malaysia (USM), E&O through its subsidiary E&O Property (Penang) Sdn. Bhd. (EOPP), Macro Dimension Concrete Sdn. Bhd. (MDC) and University of Plymouth (UP) United Kingdom are collaborating to spearhead an ecoengineering research project that will provide an improved habitat for species along the coastlines on Penang island.